On the Combined Administration of Streptokinase and Pancreatic Trypsin Inhibitor - Verstraete, M; Vermylen, J; Vermylen, C; De Vreker, R. A (Thrombosis and Haemostasis, 1964)
Preliminary results on the modification of blood fibrinogen level and plasma plasminogen value and fibrinolytic activity during combined administration of streptokinase and pancreatic trypsin inhibitor are presented. Not only fibrinogen fall but also plasminogen depletion is inhibited.